2023
DOI: 10.3389/fneur.2022.1078185
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral trans-facial vein-superior ophthalmic vein to embolize cavernous sinus dural arteriovenous fistulas

Abstract: Cavernous sinus dural arteriovenous fistula (CS-DAVF) is an abnormal communication between the CS and dural arteries from the internal carotid artery and external carotid artery. CS-DAVFs are not uncommon. The preferred treatment for most CS-DAVFs is transvenous embolization (TVE), which can achieve a high cure rate with few complications. The trans-inferior petrous sinus (IPS) route from the internal jugular vein to the CS is the favorite and most direct route to perform TVE in the great majority of CS-DAVFs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…[ 2 , 9 ] However, there are some cases in which the IPS is occluded. [ 13 , 15 ] There is an alternative approach to reach the CS through the occluded IPS, but the success rate is 54–80%,[ 4 , 13 ] and there have been some cases that are difficult to treat. Various approaches other than IPS have been reported,[ 2 , 11 ] including FV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 2 , 9 ] However, there are some cases in which the IPS is occluded. [ 13 , 15 ] There is an alternative approach to reach the CS through the occluded IPS, but the success rate is 54–80%,[ 4 , 13 ] and there have been some cases that are difficult to treat. Various approaches other than IPS have been reported,[ 2 , 11 ] including FV.…”
Section: Discussionmentioning
confidence: 99%
“…[1,3,8,10] One problem with this approach is that the FV is a long vessel with strong tortuosity, so it is necessary to select a catheter and connector appropriately. It has been reported that about 9% of cases drain into the external jugular vein, [5,15] so it is important to evaluate the approach route using preoperative CTV. In addition to CTV, magnetic resonance imaging and 3D-digital subtraction angiography (DSA) are also useful for preoperative assessment of the approach route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation